Faktor-faktor yang Mempengaruhi Pola Konsumsi Rumah Tangga Keluarga Miskin di Desa Tertinggal Kabupaten Aceh Tengah - Dian Alasta Selian; Miftahul Jannah (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2018)
This study aims to explain the factors that influence the consumption patterns ofpoor family households in underdeveloped villages of Central Aceh District. The authorwants to find out the effect of income, education and environment of residenceon consumption patterns of the people in the villages of Kala Wih Ilang and Arul Badak. This study uses a quantitative approach employing primary data from 67 sample of 200 households. This study uses multiple regression tests. The results show that income and education have positive and partially siginificant effects on consumption behaviour with t count > t table (3.637>1.996 and 6.226>1.999 respectively) while environment has a negative effect with t count<t table (1.988> 1.996). The results of F test is greater that f table with 25.582>2.75 so that the independent variables simultaneously affect the dependent variable.